Source of polycyclic aromatic hydrocarbons (PAHs) in rainwater and effect on the health of the population: the case of the District of Abidjan in the South of Ivory Coast - Brou Richmond Konan; Véronique Yoboue; Bernard Adiaffi; Mohamed Diaby; Yéï Marie Solange Oga; Adama Bakayoko; Sylvain Gnamien; Sékou Keita; Julien Bahino; Money Ossohou (Journal of Water and Health, 2022)
Rainwater pollution in urban areas is a real phenomenon globally, particularly in developing countries. This study aims to trace the origin of polycyclic aromatic hydrocarbons (PAHs) in the Abidjan district's rainwater and to evaluate the health risk to the population. Ten water samples were collected at two sites during the dry and rainy seasons over a 2-year period. The use of molecular indices and profiles as well as Spearman's correlation matrix revealed that the pyrolytic sources, such as wood combustion as well as road traffic, remain the main sources of these pollutants in the water. The risk assessment revealed a higher risk of skin cancer in children. HIGHLIGHTS Sources of polycyclic aromatic hydrocarbons (PAHs) in rainwater have been identified.; The C13 isotope to the confirmation of PAH sources in rainwater has been contributed.; Children have a higher risk of skin cancer than adults.; There is a seasonal variation of PAH concentartions in rainwater.; There is an annual variation of PAH concentrations in rainwater.;